Applying the elaboration likelihood model to analyze the effects of depression public service announcements among Malaysian College - Jin, Yu Fan; Hashim, Norliana (Global Academic Excellence, 2021)
As depression became an increasing contributor to the global disease burden, there is a demand for the public to understand depression disorder and reduce stigmatized attitudes about it. Especially, the prevalence of depression among college students is extremely higher than the general population; thus, it is essential to study among college students. Specifically, the utilizing of the health Public Service Announcement (PSA) is aiming to raise public awareness about health issues. Thus, this study emphasized on Depression Public Service Announcement and its effectiveness. By utilizing the Elaboration Likelihood Model (ELM), this study examined the consequences of the dual-process method towards stigmatized attitude changes about depression among students at a Malaysian public university. Cluster sampling technique was used to select respondents and a total of 185 respondents participated in two groups of experiments. Respondents in each group were exposed to two different DPSAs with either high-quality depression messages or low-quality depression messages. Attributional Questionnaire (AQ) was adapted to measure respondents’ attitudes toward depression, and a set of questionnaires based on Reynolds’s study was applied to evaluate the information processing approach used. Lastly, the results demonstrated that D-PSA with a high-quality message elicits higher elaboration of respondents and less stigmatized attitudes. Conversely, D-PSA with low-quality messages elicits lower elaboration and more stigmatized attitudes about depression.